(untitled) (Research, Society and Development, 2021)
Retirement is an issue that has left many Brazilians unsure due to the changes in the rules of the social security regime that have occurred recently. This will lead many individuals to look for alternatives to ensure sufficient income to survive post-retirement. Thus, the purpose of this study was to analyze the behavior of academics at a public university located in Minas Gerais, in relation to the formation of a financial reserve for retirement. The specific objectives were to describe the profile of academics, verify their level of knowledge about financial education, analyze their financial behavior and learn how they intend to form a specific retirement reserve. The hypothesis was that academics still did not consider the formation of a financial reserve for use in post-work life important and therefore did not make a reserve for this purpose. A descriptive research with a quantitative approach was carried out, whose information was collected by questionnaire. It was identified that those surveyed were predominantly young, female and were already inserted in the job market. They did not use credit cards frequently, they had control over their spending, they considered themselves controlled in the management of their finances and with sufficient knowledge for adequate financial management. They did not have much knowledge about social and private pensions, however, they knew about investments such as savings, stocks, movable and real estate. Although they consider the formation of a financial reserve to be used in the post-employment phase important, they had not yet started the formation of this reserve, despite studying at a public university, therefore without monthly fees, and already being in the labor market.